Historic Zeyrek District, Fatih , Istanbul - Fatma - Sedes (Black Book)
Major factors which effect the change of -physical formation in historical Zeyrek- Istanbul are the fires that occurred in various periods and their destructions beginning from 1960’s. Gradually increasing immigration from rural areas to urban areas with industrialization was also another major factor. Though there were always developing activities in walled city, beginning from the second half of 19th century to the end of 20th century these developments caused the disappearance of many of the cultural assets, streets and neighborhoods. The factors which caused to a destruction in Zeyrek in those days are very important, because traditional Ottoman wooden architecture was going into extinction. So the samples of traditional Ottoman wooden architecture and restoration programs on such buildings gained great importance. Within this context, the Governorship of Istanbul, Istanbul Metropolitan Municipality, Istanbul 1st Regional Directorate for Foundations, Fatih Municipality and by partnership with several related non-governmental organizations the restorations have been carried out, and the restoration works of the Molla Zeyrek Mosque(Pantocrator Church) is being completed by the Istanbul Metropolitan Municipality and Istanbul 1st Regional Directorate for Foundations.